CHRONIC CHOLESTASIS IN INFANCY - Daniela Patrichi (Amaltea Medical Publishing House, 2009)
This article focuses on the few disorders that produce chronic cholestasis in infants. The author presents: definition and pathophysiology of cholestasis; the consequences of cholestasis; an approach to diagnosis of cholestasis in infancy and childhood; the differential diagnosis of chronic cholestasis in infancy (chronic obstructive cholestasis; chronic cholestasis in association with ductal paucity; chronic hepatocellular cholestasis).